Up-regulated IL-17 and Tnf signaling in bone marrow cells of young male osteogenesis imperfecta mice - Shao, Chenyi; Liu, Yi; Li, Jiaci; Liu, Ziyun; Zhao, Yuxia; Jing, Yaqing; Lv, Zhe; Fu, Ting; Wang, Zihan; Li, Guang (PeerJ, 2022)
Osteogenesis imperfecta (OI) is a congenital bone dysplasia mainly caused by either defective production or assembly of type I collagen. The skeletal phenotypes especially fractures are often seen in OI adolescents. Studies have found that an increased number of osteoclasts and excessive bone resorption existed in collagen-related OI, which has not been well understood. Emerging evidence has suggested that inflammation may be associated with OI. We speculated that the bone marrow (BM) niche had similar inflammatory changes and performed RNA-sequencing (RNA-seq) in BM cells derived from young male mice to analyze the related differentially expressed genes (DEGs) and pathways. Data showed that there were 117 shared DEGs (Q ≤ 0.05, |log2FC| ≥ 1) in BM cells isolated from two types of OI murine models that respectively simulate different OI types. Gene Ontology (GO) (Q ≤ 0.05) analysis, Kyoto Encyclopedia of Genes and Genomes (KEGG) (Q ≤ 0.05) analysis and real-time PCR validation indicated the dysregulated biology process of cellular response to interferon (Ifn) together with upregulated IL-17 signaling, tumor necrosis factor (Tnf) signaling and osteoclast differentiation in OI BM niche. Either defective collagen production or abnormal collagen assembly shared similar alterations in gene profiles and pathways involving inflammation and osteoclast activation. Data presented here not only contributed to understanding of the mechanism of the enhanced bone absorption in the bones of OI, but also provided more evidence to develop potential anti-inflammation therapies.
Keywords: Osteogenesis imperfecta; Bone resorption; RNA sequencing; Bone marrow; Inflammation